Reliability of Estimation of HBA1C for Diagnosing Gestational Diabetes - Nusrat Manzoor, Zia Ullah, Shoaib Ahmed, Asma Kazi, Farukh Bashir, Bakhtiar Hassan Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Gestation Diabetes mellitus is a condition that, if left untreated, can have adverse effects not only on the mother but also on the unborn child. Even though the oral glucose tolerance test (OGTT), which is the typical method of screening for gestational diabetes in pregnant women and has been widely used and recognised for a number of decades, there is still a need for a test that is both more accurate and simpler to administer in order to diagnose GDM. This is the case despite the fact that the standard method involves an OGTT Subjects and Methods: In this prospective observational study, OGTT and HbA1c were performed in 400 antenatal women between 24 and 28 weeks of gestation; the pregnant women were followed up thereafter. Repeat OGTT and HbA1c were done in women with GDM at 6 weeks postpartum. Results: Among the 400 women, 52 were diagnosed with GDM, for an incidence of 9%. The mean HbA1c level in women with GDM was 6.2 – 0.6%, whereas it was 5.4 – 0.5% in those with normoglycemia. Women with GDM had a higher incidence of pregnancy-related complications compared with normoglycemic women. An HbA1c cutoff of 5.3% had a sensitivity of 95.6% and a specificity of 51.6% for the diagnosis of GDM and would have avoided OGTT in approximately half of antenatal women, while missing 5% of the women. However, those with an abnormal HbA1c will require a confirmatory OGTT, as 50% of normoglycemic women would be misclassified as having GDM by this approach. On repeat testing postpartum, two of 52 women (4.4%) had overt diabetes mellitus, whereas five (11.1%) had impaired glucose tolerance. Conclusions: Although HbA1c cannot replace OGTT in the diagnosis of GDM, it can be used as a screening test, avoiding OGTT in approximately 50% of women, if a cutoff of 5.3% is used. The findings of all of these trials make it abundantly evident that the HbAlc test is superior than the traditional OGTT in a number of important respects. The great reproducibility of the HbAlc assay, improved instrumentation and standardisation of the HbAlc assay, less biological variability, and the fact that it is not affected by short-term changes in lifestyle are all factors that contribute to these advantages. It is possible to use it as a primary screening test for all pregnant women due to the fact that the patient does not need to prepare significantly for the test and that it takes less time. If, on the other hand, the HbAlc result is discovered to be greater than the reference range, then it is absolutely necessary to perform a confirmatory test in order to establish a diagnosis of GDM. It is anticipated that HbAlc will be able to function as a diagnostic marker in the not-too-distant future. Keywords: GDM; HbAlc.